An investigation of generative data augmentation for bioacoustics classification - Herbst, Charles Daniel (Stellenbosch : Stellenbosch University, 2025)
Herbst, C. D. 2025. An Investigation of Generative Data Augmentation for Bioacoustics Classification. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/04515a96-6fb4-46aa-88ad-bdd23dd377b6